The Institutional Trap of the Reproduction of Intellectual Capital - P. V. Terelyansky; S. M. Malkarova (Открытое образование (Москва))
Purpose of the study. The inability to avoid digital segregation in access to educational technologies and content at the level of individuals, families, communities, and states plunges entire nations and peoples into an institutional trap (lock-in effect) of the reproduction of intellectual capital. To understand the degree of immersion in such an institutional trap, it is necessary to search for appropriate indicators and develop a new index based on them, which would increase the ability of the UN Human Development Index to reflect the level of development of society, considering the realities of the fourth technological revolution.Materials and methods. One of the essential parts of the Human Development Index is the composite index “Education for universal development”, which includes such quantitative indexes as the average duration of education and the expected duration of education of the population. Unfortunately, these indexes do not give an idea of the quality of the education provided: the availability of modern educational technologies, the accessibility to the latest educational content, the ability to interactively change national educational content, the possibility of using information and communication technologies for education, and more. The “Digital segregation of access to education” index, proposed by the authors, is closely related to the “Education for all development index” and expands its scope by including individuals with higher education who can form the core of research in the future specific country.Results. The insignificant fact of uncontrolled migration of an individual as a carrier of some particle of national intellectual capital creates a problem much more systemic than a simple “brain drain”. The countries from which the brain drain occurs not only lose specific gifted individuals and the individual intellectual capital associated with them but also lose the ability to reproduce the joint intellectual capital of the nation within the country. In the conditions of open borders and general globalization, there are one-sided transfer funnels that allow the holder of individual intellectual capital to leave the donor country and be integrated into the scientific and production structure and the general national capital of the recipient country without any obstacles. At the same time, the reverse movement of intellectual capital, as a rule, is impossible. The authors describe the mechanism of a one-sided funnel during the migration of intellectual capital (individual and national), which triggers positive feedback that prevents the donor country from increasing national intellectual capital and forms an institutional trap for the reproduction of intellectual capital.Conclusion. The authors continue to work on optimizing and supplementing a set of indicators for inclusion in the composite index “Digital segregation of access to education” and establish the weight of indicators in the index. The open questions are as follows: the search for a set of indicators, the formation of a necessary and sufficient set of indicators, the identification of correlation dependencies and the establishment of a close relationship between indicators, the development of a hypothesis about the unevenness of indicators, an expert assessment of establishing the weight of indicators in the index, determining the method for aggregating a set of indicators into an index.